The nineteenth century - Louis, William Roger, 1936-; Low, Alaine M; Porter, Andrew (Oxford history of the British Empire companion series, 1999)
Volume III of The Oxford History of the British Empire covers the long nineteenth century, from the achievement of American independence in the 1780s to the eve of world war in 1914. This was the period of Britain's greatest expansion as both empire-builder and dominant world power. The volume is divided into two parts. The first contains thematic chapters, some focusing on Britain, others on areas at the imperial periphery, exploring those fundamental dynamics of Britishexpansion which made imperial influence and rule possible. They also examine the economic, cultural, and institutional frame.